Carbon dots from PEG for highly sensitive detection of levodopa1. Issue 11 (21st March 2015) - Li, Hao; Liu, Juan; Guo, Sijie; Zhang, Yalin; Huang, Hui; Liu, Yang; Kang, Zhenhui
<x xml:space="preserve">Abstract</x> Fluorescent carbon dots (CDs)/tyrosinase hybrid as a fluorescent probe for efficient, fast and sensitive detection of levodopa.